Development of nickel-doped pyrolysed metal-organic framework (MIL-101) catalysts for fatty acid deoxygenation reaction - Chang, He (2024)
The deoxygenation (DO) reaction is the fundamental step in producing high-quality green diesel, wherein the catalyst plays a pivotal role in this process. However, several challenges are still associated with catalysts employed for DO to produce green diesel. Firstly, the issue of active metal leaching significantly hampers both catalytic activity and its efficiency. Secondly, coke formation on the catalyst during DO reactions leads to catalyst deactivation. MIL-101-Cr is one of the most well-studied chromium-based metal-organic frameworks (MOF) comprising metal chromium ion and terephthalic acid ligands. It has a high specific surface area and a well-ordered tunable porous system. Therefore, MIL-101-Cr catalysts can enhance interaction with an active metal dopant, thereby preventing metal from leaching in the DO process. Additionally, the abundant acid-base sites of MIL-101-Cr catalysts can effectively avoid unexpected coke formation and improve the stability of catalysts. In this study, palmitic acid (PA) was employed as the model compound to produce green diesel through hydrodeoxygenation (HDO) using nickel-doped pyrolyzed MIL- 101-Cr (Ni/P-MIL-101) catalysts. The preparation was started with pristine MIL-101 synthesis (MIL-101) via the solvothermal method, followed by Ni doping via the wet impregnation method. Then, the obtained catalyst precursors were pyrolyzed to produce pyrolyzed MIL-101 (P-MIL-101) and 4-25 wt% Ni/P-MIL-101.The HDO reaction optimization was performed using P-MIL-101 catalysts with different Ni loading. The results demonstrated that 100% conversion of PA and hydrocarbon selectivity were achieved by Ni loading > 8 wt.% on P-MIL-101 catalysts. Furthermore, the Ni/P-MIL-101 catalyst exhibited excellent stability and reusability in the PA HDO reaction. Notably, 14 wt.% Ni-doped P-MIL-101 catalysts could recycle up to 15 times, respectively, without losing their catalytic activity, and nearly 100% alkane yield was achieved, contributing to its most acidic sites and minimal metal leaching. The respond surface method (RSM) analysis showed that the highest green diesel yield could reach up to 94.4% in palm fatty acid distillate (PFAD) HDO reaction under the optimized conditions of temperature of 385 ℃, reaction time of 119 min, H2 pressure of 3 MPa and 4.5 wt.% catalyst loading. The property testing of produced green diesel also confirmed that it fully complied with ASTM D6751 and European EN14214 international biodiesel standards. In the second part of the research, the DO reaction of PFAD was investigated under an N2 atmosphere using a P-MIL-101 catalyst with different Ni loading. The PFAD DO reaction was optimized in the range of reaction temperature (280~360 ℃), reaction time (1~5 h), and catalyst loading (1~7 wt.%). The results demonstrated that 14 wt.% Ni/P-MIL-101 catalyst exhibited superior catalytic activity in converting PFAD into paraffin hydrocarbons. The highest hydrocarbon yield (93%) and selectivity of n- (C15+C17) (91%) were achieved at 320 ℃, 4 h and 3 wt.% catalyst loading. High DO activity was attributed to acidity, specific surface area, and pore size of the catalyst, and decarbonylation was the main pathway in the PFAD DO process. Furthermore, our findings also indicated that the 14 wt.% Ni/P-MIL-101 catalyst exhibited excellent reusability and regeneration ability due to its most acidic sites and minimal metal leaching, which makes it an ideal candidate for the production of green diesel.